Relationships between Personal and Collective Place Identity and Well-Being in Mountain Communities - Knez, Igor; Eliasson, Ingegärd (Frontiers in Psychology, 2017)
The aim was to investigate the relationships between landscape-related personal and collective identity and well-being of residents living in a Swedish mountain county (N = 850). It was shown that their most valued mountain activities were viewing and experiencing nature and landscape, outdoor recreation, rest and leisure, and socializing with friends/family. Qualitative analyses showed that the most valued aspects of the sites were landscape and outdoor restoration for personal favorite sites, and tourism and alpine for collective favorite sites. According to quantitative analyses the stronger the attachment/closeness/belonging (emotional component of place identity) residents felt to favorite personal and collective sites the more well-being they perceived when visiting these places. Similarly, the more remembrance, thinking and mental travel (cognitive component of place identity) residents directed to these sites the more well-being they perceived in these places. In both types of sites well-being was more strongly predicted by emotional than cognitive component of place-identity. All this indicates the importance of person-place bonds in beneficial experiences of the outdoors, over and above simply being in outdoor environments.